1998
DOI: 10.1074/jbc.273.27.16953
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin Regulates Anchorage-independent Growth and Survival in Oral Squamous Cell Carcinoma Cells

Abstract: Integrin-basement membrane interactions provide essential signals that promote survival and growth of epithelial cells, whereas loss of such adhesions triggers programmed cell death. We found that HSC-3 human squamous carcinoma cells survived and grew readily as monolayers, but when they were suspended as single cells, they ceased proliferating and entered into the apoptotic death pathway, characterized by DNA fragmentation. In contrast, if the suspended carcinoma cells were permitted to form E-cadherin-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(197 citation statements)
references
References 54 publications
9
182
0
6
Order By: Relevance
“…This is supported by the observations that (a) AT3.1 cells are closely apposed in free suspension aggregates but separated by matrix in agarose gels ( Figure 4A,C), and (b) the adhesion holding together the large spheroids is not immediately reversed upon removal from the gel. Although formation and compaction of spheroids can be mediated by E-cadherin (Kantak and Kramer, 1998;St. Croix et al, 1998) it has been shown that AT2.1 and 3.1 cell lines do not express E-cadherin (Bussemakers et al, 1992).…”
Section: Morphological Differences May Results From the Stress Responsementioning
confidence: 99%
“…This is supported by the observations that (a) AT3.1 cells are closely apposed in free suspension aggregates but separated by matrix in agarose gels ( Figure 4A,C), and (b) the adhesion holding together the large spheroids is not immediately reversed upon removal from the gel. Although formation and compaction of spheroids can be mediated by E-cadherin (Kantak and Kramer, 1998;St. Croix et al, 1998) it has been shown that AT2.1 and 3.1 cell lines do not express E-cadherin (Bussemakers et al, 1992).…”
Section: Morphological Differences May Results From the Stress Responsementioning
confidence: 99%
“…Their finding that caspases have the capacity to cleave b-catenin proteolytically at the N-and C-terminal, which will reduce a-catenin binding, release actin filaments and reduce cell -cell interaction, indicates that b-catenin has an important role at a late stage of apoptosis. Studies on oral squamous cell carcinoma cells also indicate that cadherin-mediated adhesion promotes anchorage-independent growth and suppresses apoptosis (Kantak and Kramer, 1998). A functionally intact cadherin-b-acatenin complex in ovarian cancer could make the cancer cells less susceptible to apoptosis and thereby favour growth.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of metastasis, intercellular contact mediated through the cell adhesion molecule E-cadherin appears to prevent apoptosis (Kantak and Kramer, 1998;Day et al, 1999). There is growing evidence to suggest that osteopontin may also inhibit apoptosis during metastasis.…”
Section: Discussionmentioning
confidence: 99%